Analysis Of The Effect Of Financial Performances And Macroeconomic Indicators To Financial Distress - Anggraeni, Aninda; Priantinah, Dr. Denies; Shaikh, Dr. Mohsin (The journal of contemporary issues in business and government, 2021)
The current study investigates the effect of financial performances and macroeconomic indicators on financial distress predictions in real estate sector organisations on the Indonesia Stock Exchange during the period 2015-2017. This study used the Springate Model as a measurement of corporate financial distress and used logistic regression analysis. The results of the study found that: (1) Current ratio had a favorable effect on financial distress conditions, while the quick ratio had a unfavorable effect on financial distress conditions. (2) Net profit margin and return on assets of the two variables has a positive effect on financial distress conditions. (3) Debt ratio and debt to equity of the two variables does not affect the financial distress condition. (4) Macroeconomic indicators that are proxied by inflation, interest rates and exchange rates based on the results of the research of the three variables do not affect financial distress conditions.